TEKNOLOGI DAN KELEMBAGAAN PERBENIHAN UBIKAYU UNTUK MENDUKUNG INDUSTRI MOCAL (MODIFIED CASSAVA FLOUR) DI JAWA TENGAH - Retno Pangestuti; Sarjana Sarjana (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
MOCAL is descendant product from cassava, which apply principal modification of cassava cell by microbe fermentation. MOCAL can substitute wheat flour in many foods, namely, noodles, bread, cakes, and other cakes at varying levels of substitution. The increase of wheat flour price encourages food processors looking for cheaper substitute materials, namely, MOCAL. In response to these trends, the Central Java government plans to develop 51 industrial clusters of MOCAL with plasma core model. Supports the plan, efforts should be made to improve the productivity of cassava farming. Because of the lack of high quality seeds, farm productivity of cassava in Central Java has not been optimal. Cassava breeding centers of government has released several high yielding varieties of cassava, but the propagation activities have not grown well. This paper provides an overview of the basic technology on seed propagation of cassava and institutional guidelines of cassava seed production. To support MOCAL industry, cassava seed supply should fulfill the six rights, namely the right varieties, the right quality, right quantity, right time, right place, and the right price. To produce high quality seeds, the seed propagation should follow the standard procedures of good cassava seed production, ranging from stage of selection and preparation of breeder seed, land preparation, planting, crop maintenance, harvesting, and post harvest handling. To fulfill the needs of seeds with a uniform quality in large amounts, the seed production units should apply the method of rapid seed multiplication, and developed in the institutional group of farmers. To ensure a sustainable supply of seeds as needed, there should be an inter-regional seed network. The development of seed production units should be a part of MOCAL Industrial Cluster Development Program, and all stakeholders should take a role in these affairs.